[Re] articulação do sistema municipal de ensino de Cachoeira do Sul/RS: gestão democrática no cenário da política educacional - Zinn, Carla da Luz (2019)
This Professional Master's research takes part of the Basic Education Policies and Management research line of the Postgraduate Program in Public Policies and Educational Management and refers to the [re] articulation of the Municipal Education System of Cachoeira do Sul/RS. From this perspective, the following problem was established: How is the Municipal Education System [re] articulated in Cachoeira do Sul / RS and what are the perspectives that can contribute to the strengthening and quality of democratic educational management processes? Its general objective is to understand the processes of [re] articulation of the Cachoeira do Sul Municipal System / RS, with a view to contributing to the strengthening and quality of democratic educational management. The specific objectives were led in: problematizing public policies within the scope of democratic educational management; investigate possibilities of articulation practices of the Municipal Education System; and propose an Observatory Portal of Cachoeira do Sul Municipal Education, which includes a Practical Guide on the organization of the Municipal Education System and also indicators of quality. Methodological processes were anchored in the qualitative approach (FLICK, 2009; TRIVIÑOS, 1987), with research characterized as a case study (YIN, 2010) in the Municipal Education System of Cachoeira do Sul/RS. The research participants were 4 (four) members of the managing and normative body of the SME, being 1 (one) of the Municipal Secretariat of Education and 3 (three) of the Municipal Council of Education; and 43 (forty-three) managers of the Municipal Schools and Kindergarten Schools, maintained by the private initiative. For data production we used online questionnaires, semi-structured interviews, participant observation and document analysis. The research of state of knowledge based the reflection on the theme in question. Content analysis (BARDIN, 2007) was used to understand the data produced in the research. The theoretical contributions were mainly anchored in Bordignon (2013), Saviani (2014), Cury (2015), Sari (2015), Lück (2013). From the elements produced in the research, Municipal Education Observatory Portal of Cachoeira do Sul was created, in order to collaborate in the [re] articulation of the Municipal Education System of Cachoeira do Sul. The Municipal Education Observatory Portal, characterized as a product This research will enable the articulation between all the elements that make up the Municipal Education System, through the socialization of educational information to the municipal community of Cachoeira do Sul. In the Observatory, there is also a Practical Guide for Educational Managers about the Municipal Education System of Cachoeira do Sul and the Quality Indicators for its [re] articulation. However, it can be stated that for the [re] articulation of the Education System to occur, synergy is needed between the Municipal Education Secretariat, the Municipal Education Council and the Schools, maintained by the municipal government, and the Early Childhood Schools, maintained by private enterprise.